TPACK Implementation on Energy Topic: Reading Comprehension and Feasibility of Teaching Material - Zulkarnaen Zulkarnaen; Shelly Efwinda; Nurul Fitriyah Sulaeman (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
This research is the